Biological Data of Stingless Bees with Potential Application in Pesticide Risk Assessments - Dorigo, Adna; Rosa-Fontana, Annelise; Camargo, Isabella; Nocelli, Roberta; Malaspina, Osmar (Sociobiology, 2018)
Due to the current practice of intensive pesticide use in Brazil on crops with flowers that are attractive to bees, biological information about Brazilian native bees is required in order for public authorities that are responsible for environmental safety to use them for calculations of risk assessments. Thus, the present study aimed to obtain biological data on stingless bees: Melipona scutellaris, Scaptotrigiona postica and Tetragonisca angustula. The food consumed by larvae and by adults and the mass of forager workers were obtained. The results provide essential inputs for the risk assessment of stingless bee exposure to pesticides., combined with information about the concentrations of these substances in crops with flowers that are attractive to bees, may be used in risk calculations.